66-(7x+6)=7(x+2)+x

Simple and best practice solution for 66-(7x+6)=7(x+2)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 66-(7x+6)=7(x+2)+x equation:


Simplifying
66 + -1(7x + 6) = 7(x + 2) + x

Reorder the terms:
66 + -1(6 + 7x) = 7(x + 2) + x
66 + (6 * -1 + 7x * -1) = 7(x + 2) + x
66 + (-6 + -7x) = 7(x + 2) + x

Combine like terms: 66 + -6 = 60
60 + -7x = 7(x + 2) + x

Reorder the terms:
60 + -7x = 7(2 + x) + x
60 + -7x = (2 * 7 + x * 7) + x
60 + -7x = (14 + 7x) + x

Combine like terms: 7x + x = 8x
60 + -7x = 14 + 8x

Solving
60 + -7x = 14 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
60 + -7x + -8x = 14 + 8x + -8x

Combine like terms: -7x + -8x = -15x
60 + -15x = 14 + 8x + -8x

Combine like terms: 8x + -8x = 0
60 + -15x = 14 + 0
60 + -15x = 14

Add '-60' to each side of the equation.
60 + -60 + -15x = 14 + -60

Combine like terms: 60 + -60 = 0
0 + -15x = 14 + -60
-15x = 14 + -60

Combine like terms: 14 + -60 = -46
-15x = -46

Divide each side by '-15'.
x = 3.066666667

Simplifying
x = 3.066666667

See similar equations:

| 12x-x^2=12.8 | | 22r+18=32r-24 | | a+4a-21=0 | | x^2+49x-380=0 | | -4v+6v=-16 | | 4x^4+2x^3-39x^2+43x-10=0 | | 6x-8x+10=87-21+10x | | x-(-11)=18 | | -7(2t+3)=-35 | | s*4-46=-2 | | 49x+1.5=25x+3 | | 3x-7-4x+11=6x-3 | | 12a+12a+7a+7a= | | 40c+8=48c-20 | | -30=-5+5 | | 3x-7-4x+11=6x-7 | | 2f=10 | | 10+5(a-3)=9-2a | | tg(2x)=0.6 | | 2z^2-15z+7=0 | | 7(x-6)=56 | | x^2-10x+6=1 | | 7(3s+4)=133 | | 3z+3z+4z+3+4z+3=132 | | 3f=9 | | 8(2l+8)=112 | | 3x+1+1x+11=180 | | 5*(5*(5*(5+4)+3)+2)+1= | | x+13=111 | | 6k+k-3k+3=19 | | 7h+18=214 | | -2(x+7)=14 |

Equations solver categories